1999
DOI: 10.5271/sjweh.418
|View full text |Cite
|
Sign up to set email alerts
|

Repeated hand urticaria due to contact with fishfood

Abstract: Harvima RJ, Tuomisto L, Husman T. Repeated hand urticaria due to contact with fishfood. Scandd WorkEnviron Health 1999;25(2):151-152. BackgroundThe etiology of urticaria is often difficult to determine. However, in case of repeated circumsanceconnected urticaria, the reason may be easily clarifyable. Case A 5 1-year-old healthy woman repeatedly experienced occupational hand urticaria when handling fish food. An unexpected reason for the urticaria was found in that the fishfood contained histamine as a "contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These reactions can result from exposure to the seafood itself or to various non-seafood components present in the product. Such non-seafood components include various contaminants—such as parasites ( Anisakis simplex ),29 protochordates ( Hoya ),30 and algae (dinoflagellates— Hematodinium ),5 22bacteria (Vibrio),5 viruses (hepatitis A),5marine or bacterial toxins (saxitoxins, scombroid toxin, histamine),5 31 gases produced by anaerobic decomposition of fish (hydrogen sulphide),32 chemical additives (sodium metabisulphite), spices (mustard, paprika, flour additives, garlic),33 and hidden ingredients (casein)—in canned or processed fish products 3. The three most important seafood groupings containing the marine species most often consumed or handled by humans are Arthropoda, Mollusca, and Pisces (sub-phylum Chordata).…”
Section: Constituents Of Seafoodmentioning
confidence: 99%
“…These reactions can result from exposure to the seafood itself or to various non-seafood components present in the product. Such non-seafood components include various contaminants—such as parasites ( Anisakis simplex ),29 protochordates ( Hoya ),30 and algae (dinoflagellates— Hematodinium ),5 22bacteria (Vibrio),5 viruses (hepatitis A),5marine or bacterial toxins (saxitoxins, scombroid toxin, histamine),5 31 gases produced by anaerobic decomposition of fish (hydrogen sulphide),32 chemical additives (sodium metabisulphite), spices (mustard, paprika, flour additives, garlic),33 and hidden ingredients (casein)—in canned or processed fish products 3. The three most important seafood groupings containing the marine species most often consumed or handled by humans are Arthropoda, Mollusca, and Pisces (sub-phylum Chordata).…”
Section: Constituents Of Seafoodmentioning
confidence: 99%
“…Airborne fish allergenic‐components have been detected in the environment (100), explaining the capacity of fish to induce reproducible asthmatic responses in exposed workers (101–104). Fish skin contact has been reported as a cause of occupational protein contact dermatitis in food handlers (105, 106), as well as immunological contact urticaria (107–109).…”
Section: Fish Crustaceans and Molluscsmentioning
confidence: 99%
“…In fact, there have been a number of case reports of occupational urticaria due to contact with fish and shellfish among workers in the fisheries industry packaging or preparing fish products [ 12 , 13 , 14 ]. Moreover, Harvima R.J. et al identified the histamine present as a contaminant in fish and crabs as the causal agent of contact urticaria in a female worker who handled and fed fish and crabs at work [ 15 ]. However, in our study, the cause of onset of transient itchy wheals most frequently referred by the fishermen was skin contact with algae, aquatic plants and seabed sludge, whereas handling the catch seemed to play a secondary causal role.…”
Section: Discussionmentioning
confidence: 99%